2008
DOI: 10.1016/j.chom.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Tat Protein Inhibits the SIRT1 Deacetylase and Induces T Cell Hyperactivation

Abstract: Symptoms of T cell hyperactivation shape the course and outcome of HIV-1 infection, but the mechanism(s) underlying this chronic immune activation are not well understood. We find that the viral transactivator Tat promotes hyperactivation of T cells by blocking the nicotinamide adenine dinucleotide (NAD(+))-dependent deacetylase SIRT1. Tat directly interacts with the deacetylase domain of SIRT1 and blocks the ability of SIRT1 to deacetylate lysine 310 in the p65 subunit of NF-kappaB. Because acetylated p65 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(177 citation statements)
references
References 64 publications
3
160
0
1
Order By: Relevance
“…4D). Previous studies have shown that the viral transactivator Tat from HIV-1 can inhibit SIRT1 through binding to the SIRT1 deacetylase domain (46). Interestingly, cyclin T1 is an essential cofactor in Tat-mediated viral transcription, and its acetylation leads to the formation of an active form of the PTEFb complex and initiation of viral transcription (47).…”
Section: Fig 3 Enrichment and Clustering Analysis Of Kac Substratementioning
confidence: 99%
“…4D). Previous studies have shown that the viral transactivator Tat from HIV-1 can inhibit SIRT1 through binding to the SIRT1 deacetylase domain (46). Interestingly, cyclin T1 is an essential cofactor in Tat-mediated viral transcription, and its acetylation leads to the formation of an active form of the PTEFb complex and initiation of viral transcription (47).…”
Section: Fig 3 Enrichment and Clustering Analysis Of Kac Substratementioning
confidence: 99%
“…Kwon and coworkers have recently confirmed and expanded these results, by showing that this pathway is targeted and exploited by the HIV virus. The authors wished to understand the mechanism by which the HIV transcriptional activator Tat can positively regulate NFkB activity and induce IL-2 expression in infected lymphocytes [17]. In their work, they elegantly demonstrate that Tat inhibits SIRT1 enzymatic activity by binding to its acetyl-lysine-binding domain.…”
Section: Sirt1 Negatively Regulates Nfkb Activitymentioning
confidence: 99%
“…CD4, MHC-I/II, CD25, and CD28), and modifies autophagic flux. Tat has pleiotropic effects on cellular gene expression, metabolism, and signal cascades [22] that can cause T-cell hyperactivation [23] and neurotoxicity. In viral latency (Table 2), the paucity of viral protein expression appears chiefly to result from the infection of activated CD4 1 cells that later return to a resting state.…”
Section: Sequence Diversitymentioning
confidence: 99%